Implementasi Kurikulum Merdeka Belajar Pada Mata Pelajaran Pendidikan Jasmani di SMA Negeri Pontianak - Pujiarti, Vidya; Suhairi, Muhammad; Dewi, Utami (Journal Sport Academy, 2023)
This study aims to determine the implementation of the Freedom to learn curriculum in learning Physical Education Sports and Health (PJOK) in Pontianak City High Schools in implementing the Freedom Curriculum in terms of planning the learning process. implementation of the learning process. and assessment of the learning process This research is a quantitative descriptive research. The population in this study were PJOK subject teachers at SMAs throughout Pontianak City. The sample in this study were high school teachers, totaling 10 teachers. Data collection techniques using a questionnaire. The data analysis technique used is a quantitative descriptive analysis technique with percentages. Based on the results of this study, it shows that the application of the curriculum they learn in learning Physical Education, Sports and Health (PJOK) in SMAs throughout Pontianak City belongs to the high category. Learning planning already refers to the Independent Learning Curriculum, its implementation has adjusted to school conditions and children's abilities.